The Methuen Drama dictionary of the theatre - Law, Jonathan (Methuen Drama, 2011)
"The Methuen Drama Dictionary of the Theatre is an essential reference tool and companion for anyone interested in the theatre and theatre-going. Containing over 2500 entries it covers the international spectrum of theatre with particular emphasis on the UK and USA. With biographical information on playwrights, actors and directors, entries on theatres and theatre companies, explanation of technical terms and theatrical genres, and synopses of major plays, this is an authoritative, trustworthy and comprehensive compendium. Included are: synopses of 500 major plays biographical entries on hundreds of playwrights, actors, directors and producers definitions of nearly 200 genres and movements entries on over 100 key characters from plays information about more than 250 theatres and companies Unlike similar products, The Methuen Drama Dictionary of the Theatre avoids a dry, technical approach with its sprinkling of anecdotal asides and fascinating trivia, such as how Michael Gambon gave his name to a corner of a racing track following an incident on BBC's Top Gear programme, and under 'advice to actors' the sage words of Alec Guinness: 'First wipe your nose and check your flies', and the equally wise guidance from the master of his art, Noel Coward: 'Just know your lines and don't bump into the furniture.' As a companion to everything from the main stage to the fringes of theatrical fact and folklore, this will prove an irresistible book to all fans of the theatre."--Publisher's description